Current treatments for non-small cell lung cancer - Guo, Qianqian; Liu, Liwei; Chen, Zelong; Fan, Yannan; Zhou, Yang; Yuan, Ziqiao; Zhang, Wenzhou (Frontiers in Oncology, 2022)
Despite improved methods of diagnosis and the development of different treatments, mortality from lung cancer remains surprisingly high. Non-small cell lung cancer (NSCLC) accounts for the large majority of lung cancer cases. Therefore, it is important to review current methods of diagnosis and treatments of NSCLC in the clinic and preclinic. In this review, we describe, as a guide for clinicians, current diagnostic methods and therapies (such as chemotherapy, chemoradiotherapy, targeted therapy, antiangiogenic therapy, immunotherapy, and combination therapy) for NSCLC.